The Role of Islamic Values in Married Women's Employment Decisions in Deli Serdang - Khairina Tambunan; Nuri Aslami; Taqiya Zahrowaini; Susana Paixão-Barradas (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study analyzes the factors influencing employment decisions among married women in Deli Serdang from an Islamic perspective. These decisions are shaped by social, economic, cultural, and religious factors, with Islamic ethics and Sharia serving as key considerations for women's roles, especially in economic activities outside the home. Using a quantitative approach with questionnaires and literature review, the study found that employment opportunities significantly affect work decisions, followed by age and family size. While income and education have no significant individual impact, all variables collectively contribute 62.7% to these decisions. Influential factors include family economic needs, social participation, family support, and understanding of women's roles in Islam. Islam permits women to work within Sharia guidelines, ensuring dignity and fulfilling family obligations. This research highlights the balance between women's roles in family and society in line with Islamic teachings.